Experience and Attitude Toward Death in Nurses Who Give Terminal Stage Patient Care - Feride Koku; Metin Ateş (Association of Nurse Managers, 2016)
INTRODUCTION: The concept of death that develops in the minds of individuals has an effect on their lifestyle and behaviors in religious, legal and moral fields. The death incident and approach to patient in terminal stage in terms of providing a better care to those patients whose death is near is one of the most difficult aspect of health-related occupations. The purpose of the study is to determine attitudes and experiences of nurses regarding the concept of death and providing care to patients who are about to pass away. METHODS: A descriptive survey model was used in the research. In the research, survey forms were used as data collection tool. The population consists of nurses who provide care to terminal-stage patients treated in the hospitals of the province of Istanbul. A total of 250 nurses were reached within the scope of the research. 150 nurses work in state hospitals and 100 nurses work in private hospitals. The data analysis was conducted with SPSS 16 software in the research. In the analyses of the data, descriptive statistics such as frequency, percentage and mean were used. RESULTS: When the nurses were examined in terms of experiencing death incidence in the clinic they work in, it was determined that 88.8% of the nurses witnessed death, 11.2% of the nurses did not witness death and while 62.8% of the nurses took death naturally and thought that it is a truth of life, 16% of the nurses thought that death puts an end to pains. When expressions of the nurses for describing death were examined, it was observed that 17.2% of the nurses described it as an end of life functions, 19.2% as perishing, 10.4% as transition from one life to another life, 11.2% as a new beginning, 10% as eternity. While 58.8% of the nurses did not want to provide care to dying patients, it was determined that 46.9% of the nurses who wanted to provide care stated that a dying patient has the right to receive quality care and providing care is the responsibility of nurses, 36.4% of the nurses who did not want to provide care; did not want to because it leads to a feeling of desperation and sadness and 53.5% of the nurses did not want to provide care because they did not know how to communicate with the patient and his relatives about the concept of death. DISCUSSION AND CONCLUSION: According to the results obtained in this study, it was determined that the attitudes and behaviors of nurses regarding death have an effect on the care of terminal stage patients.